VISUAL EVOKED POTENTIALS OF SICK INFANTS WITH EPILEPSY - V. P. Zykov; I. M. Mosin; D. L. Safronov; E. B. Izumova; I. L. Stepanishev; O. A. Voronenko (Эпилепсия и пароксизмальные состояния)
Summary: 39 patients aged from 3 months to 3 years have been examined. The first group consisted of 19 sick infants with symptomatic epilepsy, the second – 10 infants with motor defect without epilepsy, the third – 10 healthy infants. The maximum delay of latency (37,4 ± 30 мс) of component Р100 of the visual evoked potentials and consequently more expressed disturbances of carrying out of impulses on visual ways, are taped in group sick of a symptomatic epilepsy of early age. The given changes had statistically significant differences (P <0,001) with those at children without a pathology of nervous system. At patients with impellent disturbances delay of latency and decrease of amplitude have been less expressed, than at patients with a symptomatic epilepsy, but differences of indicators of amplitude were doubtful. 32% of patients with symptomatic epilepsy have been diagnosed to have сortical visual impairments with disturbance of behavioural visual reactions, 67 ± 14,2 ms accurate delay of latency, 4,6 ± 3,0 mcv decrease of amplitude of the main visual evoked potentials component P100 and optic nerve hypoplasia. Delay of latency and decrease of amplitude of the main visual evoked potentials component are criterions’ of severity of sick infants’ symptomatic epilepsy course.